Social partnership on the labour market, virtual job fair - Luzgina, Elena (2020)
ABSTRACT Virtual job fairs are an online process where employers and job seekers meet each other in a virtual environment, using chat rooms, teleconferencing, webcasts, webinars and email to share information about work. Relatively new trends are so-called online job fairs or virtual job fairs. The use of modern technologies makes it possible to hire staff more efficiently than traditional recruitment methods. The article deals with modern methods of personnel attraction in the organization, such as online recruiting and social recruitment. According to the results of content analysis the scale and factors of internet usage by employers for personnel recruitment and by job seekers for job search were estimated. The analysis showed that the requirements and requests of employees and employers published on the Internet are generally the same. Keywords job fair, employment, labour market, youth, university, labor socialization and adaptation ABOUT THE AUTHOR/S Elena Luzgina Petrozavodsk State University luzgina.e.n@gmail.com My name is Elena Luzgina, a PhD in sociology. I work as a senior lecturer at Petrozavodsk State University, Russia. The sphere of my scientific research is aimed at studying the balanced development of society. In particular, I have carried out sociological research to study the quality of education and labor sphere." New Future of Work ’20, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).